Pengaruh Kualitas Pelayanan dan Ambience terhadap Kepuasan Pelanggan pada Smiljan Space Bintaro - Putri, Bunga Nadya; Pradhipta, RMW. Agie; Hutagalung, M.Husen (Jurnal Pariwisata, Bisnis dan Digital; Vol 2 No 2 (2026): Jurnal Pariwisata, Bisnis dan DigitalDO - 10.30647/jpbd.v2i2.2092, 2026)
This study aims to analyze the effect of service quality and price on customer satisfaction in a culinary business. The research method used is a quantitative approach with data collection techniques through questionnaires distributed to 100 respondents who are customers. Data analysis techniques include validity test, reliability test, coefficient of determination test, and partial test (t-test) using statistical software. The results show that service quality and price have a positive and significant effect on customer satisfaction. This is evidenced by the significance value being less than 0.05 and the coefficient of determination indicating that the independent variables are able to explain the dependent variable quite well. In the discussion, it is found that fast and friendly service as well as prices that match product quality are the main factors in increasing customer satisfaction. The conclusion of this study is that improving service quality and setting competitive prices can significantly increase customer satisfaction. The suggestion is that business owners should continuously improve service quality and regularly evaluate pricing strategies to meet customer expectations.   Keywords : : service quality, price, customer satisfaction, quantitative research